ANALISA PERLAKUAN AKUNTANSI PENDAPATAN (STUDI PADA PT. CAD SOLUSINDO) - Rahmalia, Dinda; Indriyani, Meliana; Purwanti, Rica Dwi; Putri, Salva Erena; Azizah, Uswatun (Jurnal Ekonomi & Bisnis, 2024)
The research was carried out at PT. CAD Solusindo. This research was conducted to see how accounting treats profits at PT. CAD Solusindo. This type of research uses qualitative data methods. The analysis method used is a descriptive method. The data collection technique in this research is documentation with primary data sources, namely the 2022 financial report, namely the profit and loss report. The research results show that the liquidity ratio has frozen. This is caused by an increase in current debt from year to year, so this shows that the company's performance is not good. The profitability ratio from year to year for each company shows an increase. This increase was caused by sales increasing from year to year. This shows that the company's performance is getting better because it is able to increase profits. A solvency ratio that shows an increase means the company is able to cover its long-term debts. This increase was caused by the increasing total assets from year to year. The activity ratio has increased, this means that the company's performance is increasingly increasing and the company is able to optimize the use of activities.